2022
DOI: 10.1097/gox.0000000000004706
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Free Fibular Flap for First Metatarsal Reconstruction

Abstract: Summary: Beyond being aesthetically unpleasing, metatarsal defects have been known to lead to several patient concerns such as intermetatarsal malpositioning and metatarsalgia. There are several reconstructive techniques that have been utilized for reconstruction of bony defects in the foot, including the free dorsal toe flap and dorsal metatarsal perforator flap. Our institution has utilized the free fibular flap for surgical management pertaining to tarsal reconstruction. Our study looks to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Although several case reports are presented about foot reconstruction, none of them mentioned reconstruction of the arches and evaluated its importance on gait parameters. 15,17,27 Here, our 3-dimensional gait analysis results showed that acceptable foot arch reconstruction is achievable using free vascularized fibula flap. Dynamic podography revealed similar pressure distribution with the uninjured foot, without any increased pressure areas.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Although several case reports are presented about foot reconstruction, none of them mentioned reconstruction of the arches and evaluated its importance on gait parameters. 15,17,27 Here, our 3-dimensional gait analysis results showed that acceptable foot arch reconstruction is achievable using free vascularized fibula flap. Dynamic podography revealed similar pressure distribution with the uninjured foot, without any increased pressure areas.…”
Section: Discussionmentioning
confidence: 63%
“…Despite this importance, the arches of the foot are generally underestimated during the foot reconstruction. Although several case reports are presented about foot reconstruction, none of them mentioned reconstruction of the arches and evaluated its importance on gait parameters 15,17,27 . Here, our 3-dimensional gait analysis results showed that acceptable foot arch reconstruction is achievable using free vascularized fibula flap.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations